2013
DOI: 10.1016/j.juro.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status and Postoperative Morbidity in Older Women with Prolapse

Abstract: As defined by ASA class, preoperative functional status is significantly associated with postoperative length of stay and complications. Preoperative functional status is useful for predicting postoperative outcomes in older women who undergo pelvic organ prolapse surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Surgical methods are commonly used to treat urinary incontinence in this age group. Recent studies suggest that the presence of coexisting disabilities is associated with worse functional outcomes following surgery . When planning treatment options for women with urinary incontinence, surgeons need to be cognizant of the possibility of worse outcomes in women with urinary incontinence when co‐existing disabilities are present.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical methods are commonly used to treat urinary incontinence in this age group. Recent studies suggest that the presence of coexisting disabilities is associated with worse functional outcomes following surgery . When planning treatment options for women with urinary incontinence, surgeons need to be cognizant of the possibility of worse outcomes in women with urinary incontinence when co‐existing disabilities are present.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data, preoperative hematocrit, POP-Quantification Stage (23), and American Society of Anesthesiologist Class (ASA class) were obtained from the patient's chart. ASA class has been previously reported as a useful marker of functional status in orthopedic patients (24) and in women with POP (10). …”
Section: Methodsmentioning
confidence: 99%
“…Objective markers of functional status were useful predictors of worse functional outcomes following cardiac and abdominal surgery in older mostly male patients (3, 8). Data on the postoperative functional status of older women undergoing POP surgery are limited (9, 10). It remains unclear if older women undergoing POP surgery are at increased risk for worse postoperative functional outcomes and whether such outcomes can be predicted by preoperative risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Greer and colleagues demonstrated that women with impaired preoperative functional status had a 2.13-day longer length of stay (95% CI 0.57—3.70, p<0.01) and higher rates of complications (OR = 2.18; 95% CI = 1.04–4.56) even after controlling for potential confounding factors. 6 The authors used the American Society of Anaesthesiologists physical status classification, which incorporates comorbidities with physical activity measures: climbing stairs and walking city blocks; and thus, implies that impairments in lower body mobility could lead to worse surgical outcomes. Given our results indicating high prevalence (62%) of self-reported limitations in climbing stairs, it may be possible to improve surgical outcomes and shorten inhospital stays in many older women with POP if their lower body mobility is assessed and strategies are taken to improve it prior to surgery.…”
Section: Commentmentioning
confidence: 99%
“…6 The Institute of Medicine has identified the maintenance of functional status as a priority in older women receiving surgical care. 7 In addition, the Centers for Medicare and Medicaid Services are currently working on developing functional status quality measures.…”
Section: Introductionmentioning
confidence: 99%